Determinant factors for knowledge sharing of outsourced facilities management deliverables in government buildings - Safiee, Lilis Shereena; Mohammad Ali, Irwan; Mohd Radzuan, Nor Amin; Hasim, Mohamad Sufian (Universiti Teknologi MARA, Perak, 2025)
It was not until 2007 that the government of Malaysia paid additional attention to improving the national assets and facilities through outsourced facilities management (www) and maintenance services as part of the overall public delivery system improvement. An effective knowledge management (KM) is needed to guarantee that the quality of public assets is not compromised despite the costly government services, as compared to the private sector. Poor service delivery, lack of communication and weak performance management are among the hitches reported from the OFM team, which are believed to have resulted from the absence of knowledge sharing (KS) activities within the members of the organisation. This paper aims to identify the factors that determine the KS of OFM services in government buildings. Based on the Theory of Planned Behaviour (TPB), a set of questionnaires has been developed concerning past studies and distributed to OFM personnel through a self-administered online platform. 112 out of 200 responded data set is analysed through SPSS Version 28. The findings from Factor Analysis finalised 30 out of 33 proposed construct items, where training and development, organisation structure and explicit knowledge were eliminated due to low communality value. Thus, from the research, a conceptual framework is suggested that consists of five determinant factors as independent variables, namely self-attitude, nature of knowledge, motivation to share, organisation culture and opportunity to share, while KS towards performance improvement of OFM in government buildings is the dependent variable.